A strategy for the appropriation of ICT in the reconciliation of the victims of the colombian armed conflict - José Joaquín Bocanegra García (Trilogia, 2016)
the Colombian peace process includes a phase for the development of an agreement between the parties in conflict. After that, it should continue with building territorial peace through the participation of all citizens and communities. At this stage, the main goal is to promote the rights of victims. This can be achieved by developing spaces that help mediation, dialogue and action among the actors in conflict, in order to seek their reconciliation. In this scenario, information and communication technology (ICT) can play an important role in supporting these spaces. This paper proposes a strategy for the appropriation of ICT in the reconciliation of victims of the Colombian conflict. Specifically, the strategy proposes a conceptual approach for an information system that facilitates communication, interaction and presentation of ideas and arguments between the parties in conflict.